The Influence of Learning Strategies and Learning Motivation against Islamic Fikih Students Learning Results in MIN 2 Labuhanbatu - Rusydi Ananda; Heri Caniago (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The purpose of this study was to determine and describe: (1) the effect of the application of learning strategies on the learning outcomes of Islamic Fikih, (2) the influence of learning motivation on the learning outcomes of Islamic Fikih, and (3) the interaction between strategies learning and learning motivation towards the learning outcomes of Islamic Fikih. The method used in this study is a quasi-experimental method. The study population was all students of class VI MIN 2 Labuhanbatu consisting of 3 classes. The sampling technique used was cluster random sampling, in which one group of classes was conducted using collaborative learning and the other class was conducted competitive learning. Data collection techniques used are lift and learning outcomes tests. The data analysis technique used is two-way analysis of variance.  The research findings show: (1) there is an influence of learning strategies on fiqh learning outcomes. In this case the average learning outcomes of Islamic Fikih taught with collaborative learning strategies are higher than the average learning outcomes of Islamic Fikih taught with competitive learning strategies, (2) there is an influence of learning motivation on learning outcomes of Fikih. In this case, the average learning outcomes of Islamic Fikih with higher learning motivation is higher than the average learning outcomes of Fikih with low learning motivation, and (3) there is an interaction effect between learning strategies with learning motivation, where students with high learning motivation are more precisely taught using collaborative learning strategies, while students with low learning motivation are more precisely taught with competitive learning strategies.